Features of Uzbek Ganch Carving - Sardor bek Abdujalolov Abdujalolovich; Abduvohid Abdujalilov Abdujamilovich; Temirov Murodjon Anvarovich (International Journal on Integrated Education, 2021)
The article examines the features of the art of ganch carving in Uzbekistan and its significance in the development of ganch carving in our country.